CBCT study of root and canal morphology of permanent mandibular incisors in a Chinese population. (January 2014) - Liu, Jia; Luo, Jun; Dou, Lei; Yang, Deqin
Abstract Objective. To evaluate root canal morphology of permanent mandibular incisor teeth in a Chinese population using cone-beam computed tomography (CBCT). Materials and methods. CBCT images of Chinese patients were collected and 1553 permanent mandibular incisors in the images were included. The following observations on the included teeth were to determine the number of roots, root morphology and canal configuration. The root canal configurations were classified. The effect of gender on the incidence of the second canal was investigated. Results. Of permanent mandibular incisors, 86.8% had a single root with single canal. Mandibular lateral incisors (17.5%) had a higher incidence of a second canal compared with mandibular central incisors (8.9%) (p = 0.000). A slightly higher percentage of incidence of a second canal was found in males (14.6%) than in females (11.9%) (p = 0.129). Conclusions. Permanent mandibular incisors with two canals had a relatively low incidence in this Chinese population. The incidence of a second canal did not differ between males and females. CBCT is a valuable aid during root canal treatment.